PKM Khatmil Kitab Washiyat al-Mustafa li al-Imam 'Ali Karrama Allah al-Wajhah melalui Mixed Method Sorogan dan Bandongan pada Santri PDF Tingkat Ulya di Pondok Pesantren Nurul Qadim - Hasan Hasan (Universitas Nurul Jadid, 2020)
This article describes the result of community service in terms of finishing book (khatmil kitab) Abdul Wahab al-Sya'rani’s work, Washiyat al-Mustafa li al-Imam 'Ali Karrama Allah al-Wajhah, among students of the advanced level of Formal Islamic Education (Pendidikan Diniyah Formal Tingkat Ulya) in Nurul Qadim Islamic Boarding school in order to strenghten narrative of the deep understanding of religion (tafaqquh fi al-din). This program is begun from socialization of the scheduled activities to the students from class to class. It has been advanced for eight times of face-to-face teaching-learning process with using large-class-teaching (bandongan) and small-class-teaching (sorogan). Based on the community service-based program of khatmil kitab, students are able to get knowledge, to hope for blessing (tabarrukan), to worship in every Friday, and to pragmatically fulfill the productive period with giving free snacks during that activity.